Gone again [compact disc, unabridged] - Grippando, James, 1958- (Grippando, James, 1958- Jack Swyteck novel., 2016)
Sashi Burgette vanished three years ago on her way to school. The night after the teenager's disappearance, ex-con Dylan Kyle was stopped for drunk driving. An article of Sashi's clothing was found in his truck, and a police videotape of his drunken explanation under interrogation sealed his fate at trial. Now, just days from Kyle's execution, Sashi's mother visits Jack Swyteck, doing pro bono work at the Freedom Institute, and delivers shocking news: 'Sashi called me'. The police dismiss the call as a cruel hoax. The State Attorney refuses to consider the new evidence, insisting the case is closed. The governor has already signed the death warrant. An innocent man may be executed and time is running out, unless his lawyers can locate Sashi.